The influence of different methods of analysis of the effect of non-operative genuine stress incontinence treatment on final conclusions - Surkont, Grzegorz; Wlaźlak, Edyta; Stetkiewicz, Tomasz; Sobieszkoda, Dominika; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2005)
Specialists try to find methods which will help to minimize “bias” effect during analysis of effect of treatment of genuine stress incontinence. One of the way is to organize double-blind studies. During analysis of many methods of stress incontinence treatment this is not possible. Aim of the study: The aim of the study was to evaluate the influence of different methods of analysis of the effect of non-operative genuine stress incontinence treatment on final conclusions. Material and method: In this analysis we evaluated 50 patients. Before non-operative treatment and 6 months later there were done urogynecologic exams according to protocol. Analysis of the results was done according to ITT, modified ITT system and old-way of analysis. Results: Differences in percentage of cured patents were from less than 1% to around 25%. Conclusions: 1. During choosing methods of urogynecologic exam, possibility of assessing the result from the patient should be taken into account. 2. To minimize “bias” effect there should be used a few ways of analysis of the results. 3. More invasive methods of patients’ exam give less chance to obtain the women’s agreement to do the exam again.